1988
DOI: 10.1073/pnas.85.1.94
|View full text |Cite
|
Sign up to set email alerts
|

cGMP-dependent channel protein from photoreceptor membranes: single-channel activity of the purified and reconstituted protein.

Abstract: The cGMP-dependent channel protein has been purified from bovine rod photoreceptor membranes and incorporated into planar lipid membranes. At low divalent cation concentrations, cGMP stimulated single-channel current fluctuations. The probability P. of the channel being open strongly depended on the cGMP concentration (EC'50 = 31 ,IM;Hill coefficient, n = 2.3); whereas the single-channel conductance (A = 26 pS) was independent of the agonist concentration. The agonist-stimulated increase in the probability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…An analysis 35 of the open/close probability under different concentrations of 1a in 4 M KCl leads to a fitted Hill coefficient (Fig. 4b) of 9 ± 3, consistent with the self-assembly of at least nine molecules of 1a to form a functional transmembrane channel.…”
Section: Transmembrane Ion Transport Through Self-assembled Nanoporessupporting
confidence: 66%
“…An analysis 35 of the open/close probability under different concentrations of 1a in 4 M KCl leads to a fitted Hill coefficient (Fig. 4b) of 9 ± 3, consistent with the self-assembly of at least nine molecules of 1a to form a functional transmembrane channel.…”
Section: Transmembrane Ion Transport Through Self-assembled Nanoporessupporting
confidence: 66%
“…In other channel types, the channel activity is more evenly distributed among its conductance states. This is the case for the glutamate-activated channel (CullCandy and Usowicz, 1987;Jahr and Stevens, 1987) and the light-dependent channel from vertebrate photoreceptors (Hanke et al, 1988;Haynes and Yau, 1990). For the Limulus light-activated channel, both states are expressed with roughly equal frequency in some cells, although not in all cells.…”
Section: Discussionmentioning
confidence: 96%
“…In two other studies of the salamander rod channel, the smaller current level was not observed. Matthews & Watanabe (1988) (Hanke et al 1988;Bennett & Clerc, 1989;Ildefonse & Bennett, 1991), but these channels appear to have slower activation kinetics and a lower sensitivity to cGMP than the channel of salamander rods. The value of 25 pS estimated here for the open-state conductance of the channel at +50 mV is in good agreement with two previous values for the amphibian rod channel (Haynes et al 1986, -25 pS;Zimmerman & Baylor 1986, -24 pS).…”
Section: Discussionmentioning
confidence: 99%
“…The cGMP-activated channels from mammalian rod cells have been incorporated into planar lipid bilayers and expressed in frog oocytes (Hanke, Cook & Kaupp, 1988;Kaupp et al 1989;Ildefonse & Bennett, 1991), but these channels appear to have different gating kinetics from those of excised patches from amphibian rod outer segments, which show much more rapid flicker. Some channels in inner segment patches from amphibia also flicker very little (Torre et at.…”
mentioning
confidence: 99%